An enhanced lemaitre damage model and verification method for X12 alloy steel in hot forming process. (1st October 2022) - Chen, Xuewen; Du, Yuqing; Du, Kexue; Xiang, Nan; Li, Zhipeng; Tian, Xuanhe; Liu, Mengxiang
Graphical abstract: Highlights: Considering the influence of stress triaxial degree, temperature and strain rate on damage evolution, the Lemaitre high temperature damage model was established. The damage parameters of the damage model are determined by reverse optimization method. The comparison of crack initiation and propagation in FE simulation and DIC experimental results could express the good accuracy of the damage model. The damage evolution process in the down-ratio forging test was studied by using the established damage model. Abstract: One major issue is accurate prediction and effective control of crack defects, which is one of the key scientific problems in developing high-quality rotor forgings. As a result, an enhanced Lemaitre continuous damage model considering the effect of stress triaxiality, strain rate and temperature was put forward in this paper, aiming at predicting the crack initiation of rotor steel during forging process at elevated temperature. The parameters of Lemaitre continuous damage model were inversely obtained by genetic optimization algorithm according to the data of tensile test. Then, the proposed damage model was integrated into the finite element software FORGE® to delineate the hot deformation of X12 alloy steel. In order to verify the accuracy of the model, V-notch cylindrical specimens and notched tensile specimens were designed for isothermal compression test and tensile test. Digital image correlation (DIC) technology was used to capture the strain field and displacement field of specimen under elevated temperature conditions. The accuracy of the model has been verified by comparing the test results with the finite element simulation results. Finally, the down-ratio forging test of the ultra-supercritical high and medium pressure rotor was carried out. The established elevated temperature damage model was used for researching the crack defects of ultra-pressure rotor steel in forging process. By comparing the location of crack defects between down-ratio forging test and simulation, which further verified the accuracy of the proposed damage model. The results indicate that the enhanced damage model can predict the crack defects of X12 alloy steel during its hot forging process.